2019
DOI: 10.1200/jco.18.00032
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant (Chemo)radiotherapy With Total Mesorectal Excision Only Is Not Sufficient to Prevent Lateral Local Recurrence in Enlarged Nodes: Results of the Multicenter Lateral Node Study of Patients With Low cT3/4 Rectal Cancer

Abstract: Purpose Improvements in magnetic resonance imaging (MRI), total mesorectal excision (TME) surgery, and the use of (chemo)radiotherapy ([C]RT) have improved local control of rectal cancer; however, we have been unable to eradicate local recurrence (LR). Even in the face of TME and negative resection margins (R0), a significant proportion of patients with enlarged lateral lymph nodes (LLNs) suffer from lateral LR (LLR). Japanese studies suggest that the addition of an LLN dissection (LLND) could reduce LLR. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
429
9
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 354 publications
(453 citation statements)
references
References 32 publications
(31 reference statements)
11
429
9
4
Order By: Relevance
“…Although patients with LLNs had a better outcome than those with mesorectal ypN2+ disease, a previous multi-institutional study 2 from Japan showed that the survival rate of patients with LLN metastasis was similar to that of patients with pN2 status when neoadjuvant (C)RT was not performed. Importantly, LLND was highly standardized in the present series with en bloc lymphadenectomy; a previous study 15 in this field showed little benefit from limiting resection to the affected LLNs, as more than half of the patients later developed local recurrence in the same compartment.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Although patients with LLNs had a better outcome than those with mesorectal ypN2+ disease, a previous multi-institutional study 2 from Japan showed that the survival rate of patients with LLN metastasis was similar to that of patients with pN2 status when neoadjuvant (C)RT was not performed. Importantly, LLND was highly standardized in the present series with en bloc lymphadenectomy; a previous study 15 in this field showed little benefit from limiting resection to the affected LLNs, as more than half of the patients later developed local recurrence in the same compartment.…”
Section: Discussionmentioning
confidence: 90%
“…Similar data have been reported from the West, with a recent study finding a lateral local recurrence rate of 33·3 per cent at 4 years when LLNs had a short‐axis diameter of 10 mm or above. A recent multi‐institutional international retrospective study from 12 institutions reported that patients with LLNs and a short‐axis diameter of at least 7 mm had a significantly higher risk of lateral local recurrence than patients with LLNs of less than 7 mm. In addition, a recent survey showed that most radiation oncologists in the USA treat involved LLNs with curative intent and recommend treatment intensification, in the form of LLND, radiotherapy boost, or both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the very early stage of tumor progression, FN is downregulated to help tumor cells ameliorate their oncogene-or loss of TSG-induced endogenous ER stresses and evade senescent limitation of cell cycle progression. Therefore, for tumor patients in a very early clinical stage, in addition to the traditional surgery, chemotherapies, and radiotherapies or recently prevailing immune checkpoint blockade therapies [353][354][355], therapeutic strategies can be formed by inducing overexpression of FN in newly transformed tumor cells and force tumor cells into senescent state or cell cycle arrest followed by cell apoptosis, if FN is proved to be a regulator for senescent induction by enhancing ER stresses. Alternatively, tumor senescence and subsequently apoptosis can be induced circumventing alteration of FN expression level [356,357].…”
Section: Future Perspectives For Fn-targeting Therapeutic Strategiesmentioning
confidence: 99%
“…This finding supports the need for a careful analysis of LN+ during the pretherapeutic and per‐operative period to perform a complete resection. The rate of lymphatic spread with LR is inconsistent in the literature because LN recurrence and LR are frequently defined as a similar disease . Among series defining nodal and LR as two distinct diseases, the association of LN+ plus LR ranges from 1.8% to 87.5% …”
Section: Discussionmentioning
confidence: 99%